The answer / La respuesta : including a selection of poems - Juana Inés de la Cruz, Sister, 1651-1695 (Feminist Press at the City University of New York, 1994)
"Outstanding edition and translation into English of Sor Juana's intellectual tour de force. Includes an excellent introduction, chronology, notes, and critical commentary. Both scholarly remarks and Sor Juana's work are essential reading for scholars, specialists, students of all levels, and the general reader"--Handbook of Latin American Studies, v. 58.